2018
DOI: 10.1093/isr/viy014
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Cooperation on Peacemaking: Definitions, Mechanisms, and Empirical Evidence

Abstract: The literature on environmental peacemaking claims that groups in conflict can put aside their differences and cooperate in the face of shared environmental challenges, thereby facilitating more peaceful relations between them. This study provides the first comprehensive review of the widely dispersed empirical evidence on such environment-peace links. In order to do so, it distinguishes three understandings of peace and identifies four mechanisms connecting environmental cooperation to peace. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 95 publications
0
40
0
Order By: Relevance
“…The empirical success of such efforts is so far been limited ( Kelman, 2019 ). However, research on environmental peacebuilding has revealed that low-level, mutually beneficial cooperation can yield peace dividends in certain contexts ( Ide, 2019 ). Furthermore, ceasefires to deliver health benefits have at least temporally reduced armed conflict intensity on several occasions in the past ( Chattu & Knight, 2019 ).…”
Section: Theoretical Background: Grievances Opportunities and Conflimentioning
confidence: 99%
“…The empirical success of such efforts is so far been limited ( Kelman, 2019 ). However, research on environmental peacebuilding has revealed that low-level, mutually beneficial cooperation can yield peace dividends in certain contexts ( Ide, 2019 ). Furthermore, ceasefires to deliver health benefits have at least temporally reduced armed conflict intensity on several occasions in the past ( Chattu & Knight, 2019 ).…”
Section: Theoretical Background: Grievances Opportunities and Conflimentioning
confidence: 99%
“…The importance of international policy interventions, in this case in the form of international protection of certain types of migrants, also is stressed in the work on their perceptions on armed conflict by Koubi et al (2018). It is also clearly visible in the recent research on environmental peacebuilding (Krampe 2017;Ide 2018).…”
Section: Empirical Evidence On the Contested Elements Of The Disastermentioning
confidence: 99%
“…Climate change, has become an important common concern for conflict prevention and peacebuilding activities as well as development policy in general, and at the same time, migration and violent conflict are increasingly realized as undermining efforts to alleviate the economic and social consequences of climate change (Mobjörk et al 2016b;Schilling et al 2017;United Nations and World Bank 2018). Environmental peacebuilding explicitly aims to integrate environmental concerns with conflict prevention and peacebuilding (Ide 2018).…”
Section: Complementarities and Synergies Of International Policy Intementioning
confidence: 99%
“…The theory of environmental peace-building has put forward three strands of scholarship in which environmental cooperation may generate peace-building opportunities (Ogden 2018). The first concerns the prospect that environmental cooperation in places with environmental security can encourage common-pool resource management and conservation initiatives (Ogden 2018;Conca and Wallace 2009;Ide 2018;Conca and Dabelko 2002). Such initiatives can contribute to the prevention of conflicts that occur due to the over-exploitation of natural resources or livelihood insecurities due to environmental pressure (Ide 2017).…”
Section: Theoretical Background 21 Environmental Peace-buildingmentioning
confidence: 99%
“…Such initiatives can contribute to the prevention of conflicts that occur due to the over-exploitation of natural resources or livelihood insecurities due to environmental pressure (Ide 2017). The second is that collective environmental concerns can lead to a dialogue between conflicting interests, which can then spill over into different areas (Ogden 2018;Conca and Wallace 2009;Ide 2018;Conca and Dabelko 2002). For instance, the UN identifies environmental degradation as a risk factor for violent conflict, while environmental protection of common resources is recognized as a mechanism to build peace (Conca and Wallace 2009).…”
Section: Theoretical Background 21 Environmental Peace-buildingmentioning
confidence: 99%